2019
DOI: 10.1016/j.bjorl.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term functional results between standard supracricoid laryngectomy and modified technique with sternohyoid muscle

Abstract: Although there is no statistical difference in functional outcome comparisons, if rules are adhered to in preoperative patient selection, modified supracricoid partial laryngectomy can be applied safely and meaningful gains can be achieved in functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Furthermore, pharyngocutaneous fistula and surgical wound infection are frequent complications associated with increased length of hospital stay and the need for a new surgical intervention 15 . In this context, functional and structural changes and possible treatment complications impact patients' QoL, mainly in the elderly 16 . Moreover, chemotherapy and radiation therapy can be integrated into treatment and cause sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, pharyngocutaneous fistula and surgical wound infection are frequent complications associated with increased length of hospital stay and the need for a new surgical intervention 15 . In this context, functional and structural changes and possible treatment complications impact patients' QoL, mainly in the elderly 16 . Moreover, chemotherapy and radiation therapy can be integrated into treatment and cause sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of the swallowing function is another important parameter after OPHL. Oral intake has been reported to range from 3 to 45 days after surgery [ 27 ]. In our study, we identified 11.9 mean post-operative days of restarting oral feeding, consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The preservation of vocal and laryngeal function is always recommended, SCL represents one of the alternatives adopted to replace TL, because in addition to being adopted as an initial treatment, it can also be indicated in cases of extralaryngeal dissemination and local reinfections. 1,27 However, TL are currently the most indicated and adopted for tumors that have an extralaryngeal spread and in cases of local recurrence, in which no other approach can be performed. 24 OPHLs have excellent overall survival, disease-free survival and TL-free survival, in addition to having the aim of preserving laryngeal functions: phonation, swallowing and breathing.…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal cancer (LC) is the most common cancer that affects the upper respiratory tract and the second most routine among those that affect the respiratory system worldwide, second only to lung cancer. [1][2][3] Among the various types of cancers that affect the head and neck, laryngeal cancer is the most recurrent, representing 25% of all neoplasms in the area. [4][5][6] Regarding gender, this pathology predominates in males, in a ratio of 4 to 1 in relation to females.…”
Section: Introductionmentioning
confidence: 99%